A preference analysis and justification of Arabic written corrective feedback among instructors and undergraduates - Abd Hamid, Mohd Azrul Azlen; Sahrir, Muhammad Sabri; Razali, Khairil Azwar (Indonesian Journal of Applied Linguistics, 2021)
There has been extensive discussion on the need to use corrective feedback in writing within foreign language learning. Essentially, corrective feedback is one of the important tools in improving students’ skills in learning a language. This study aims to find out the preference and justification of written corrective feedback (WCF) through the use of Google Docs among instructors and students in a higher learning institute. The effects of the direct and indirect feedback with metalinguistic comments were also studied to determine their suitability in teaching and learning the Arabic language. Quantitative and qualitative data were collected to (1) identify the preferred type of feedback among instructors and students, (2) identify justification of the preferred feedback type, and (3) examine post-test score differences between types of written correction feedback. Two questionnaires were adapted and distributed to 93 first-year students and four instructors of Arabic language for Academic Writing. Two instructors and five students were interviewed to find out their justification of the preferred types of WCF. A total of 50 respondents were divided into two groups according to the type of WCF provided, and post-test scores between the types of feedback were compared to determine if there was any significant difference between the types of feedback. The findings show that instructors prefer indirect WCF with metalinguistic comments while students prefer direct corrective feedback with metalinguistic comments. Post-test scores indicate that higher scores were achieved by students who received indirect feedback with metalinguistic comments. This indicates that students are able to process indirect feedback that is supplemented with metalinguistic comments. Moreover, an online learning environment provides more opportunities for instructors to highlight the students’ errors more clearly.